Improving Knowledge, Interest, and Behavior Toward IVA Screening Through Audio-Visual Education Among Reproductive-Age Women in Ciamis - Rahman, Gita Ekaputra; Wulandara, Qanita; Gustini, Sri (Media Informasi, 2025)
Background: Cervical cancer remains one of the leading causes of death among women worldwide, despite being largely preventable through early detection methods such as Visual Inspection with Acetic Acid (IVA). However, the participation rate of women of childbearing age in IVA screening remains low, particularly in rural areas. Health education using audio-visual media has the potential to enhance knowledge, stimulate interest, and promote preventive health behaviors. This study aimed to evaluate the effectiveness of audio-visual-based education on IVA screening in improving knowledge, interest, and behavior among women of childbearing age in Gereba Village, Cipaku District, Ciamis Regency. Methods: This quasi-experimental study employed a one-group pretest-posttest design. A purposive sampling technique was used to recruit 81 women of childbearing age. Data were collected through structured questionnaires measuring knowledge, interest, and behavior related to IVA screening before and after the educational intervention. Statistical analysis was conducted using univariate and bivariate non-parametric tests, specifically the Wilcoxon Signed Rank Test. Results: The majority of participants were aged 15–44 years (88.9%), had a low level of education (60.5% did not complete high school), and were predominantly housewives (97.5%). The Wilcoxon Signed Rank Test indicated a statistically significant increase in knowledge (p = 0.000), interest (p = 0.000), and behavior (p = 0.034) following the audio-visual educational intervention. Conclusion: The study demonstrates that audio-visual education significantly improves knowledge, interest, and preventive behavior regarding IVA screening among women of childbearing age. These findings support the integration of innovative media-based education in public health strategies to enhance cervical cancer prevention efforts in rural communities